2017
DOI: 10.18203/2394-6040.ijcmph20170274
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical waste management practices in a tertiary care hospital: a descriptive study in Srinagar, Garhwal, India

Abstract: Background: Biomedical waste (BMW) is generated in every health facility, which if not disposed off properly poses a risk for health and environment. Handling, segregation, mutilation, disinfection, storage, transportation and final disposal are vital steps for safe and scientific management of biomedical waste in any establishment. The objective were to assess the biomedical waste management (BMWM) practices and knowledge regarding BMWM  in a tertiary care hospital.Methods: A descriptive study was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…This might be due to the less trained sanitation staff in the facilities. This is similar to that reported by Lohani et al [15].…”
Section: Problems With Implementationsupporting
confidence: 93%
“…This might be due to the less trained sanitation staff in the facilities. This is similar to that reported by Lohani et al [15].…”
Section: Problems With Implementationsupporting
confidence: 93%
“…In this study it was found that 71% of the participants from the government institute and 81% of the participants from the private institute had training in biomedical waste management, compared to 68% of the nurses who participated in a study done by Lohani N et al (5) .…”
Section: Discussionmentioning
confidence: 67%
“…Segregation separates different medical waste streams according to their classifications and is an essential part of the medical waste management process [9]. The essence is to separate infectious/hazardous waste from non-infectious/nonhazardous waste and prevent contamination [15]. Segregation would also reduce the quantity of infectious/hazardous waste.…”
Section: Pathological Wastementioning
confidence: 99%
“…Sharp objects are to be placed in a yellow puncture-proof container marked "sharps" with a biohazard symbol. In addition to yellow, Lohani & Dixit [15] recommended red bags for infectious waste. Baaki et al [9] suggested that pharmaceutical waste and chemicals be placed in a brown plastic bag (hospital-specific), while radioactive wastes should be placed in a lead box with the radioactive symbol.…”
Section: Pathological Wastementioning
confidence: 99%